2017
DOI: 10.3390/met7060197
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Cutting Force of Machining In Situ TiB2 Particle-Reinforced 7050Al Alloy Matrix Composites

Abstract: In situ TiB 2 particle-reinforced 7050Al alloy matrix composites are a new category of particulate metal matrix composites with improved mechanical and physical properties. At present, the study of machining in situ TiB 2 /Al composite is limited and no specific study has been presented on cutting force. Based on previous work, experimental investigation of cutting in situ TiB 2 /Al composite was carried out in this study to investigate the cutting force, shear angle, mean friction angle, and shear stress. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This effect may be due to the increase in the cutting area and removed material volume, by increasing feed rate. 43 Moreover, Xu et al 28 observed that shear angles were increased by increasing cutting speed. As a result, shear slip plane area in the primary deformation zone decreases leading to reduced cutting force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may be due to the increase in the cutting area and removed material volume, by increasing feed rate. 43 Moreover, Xu et al 28 observed that shear angles were increased by increasing cutting speed. As a result, shear slip plane area in the primary deformation zone decreases leading to reduced cutting force.…”
Section: Discussionmentioning
confidence: 99%
“…Thickness and shape of all chips were noted and chip thickness ratio (r) and shear angle (u) were determined. Shear angle was calculated using equation (4) 25,[41][42][43] tan u = r cos a 1 À sin a ð4Þ…”
Section: Measurement Of Cutting Forcesmentioning
confidence: 99%
“…However, no explanation related to thermal softening or strain hardening effects was given as compared to [59] (Figure 25Figure 25). However, Xiong et al [61] have claimed that feed rate had the most dominant effects on cutting force when micro-milling Al/TiB 2 instead of filler content or cutting speed due to their influences on increasing shear angle and decreasing friction angle while Pramanik et al [62] confirmed that the increase of material removal rate (MRR) at high feed rates contributed to cutting force escalation.…”
Section: Micromachining Of Nano-ceramic Based Nanocompositesmentioning
confidence: 99%
“…Substituting equations (3), (11), and (23) into equation (24), the final micromilling force models are obtained as equations (25) and (26)…”
Section: Compositementioning
confidence: 99%
“…By milling process, Liu et al 24 constructed a model for nanoscale particle–reinforced magnesium matrix composites, in which the particles were considered to be removed by elastic deformation and movement. Xiong et al 25 built a model to calculate the forces at the maximum cutting thickness in milling the in-situ TiB 2 /Al composite, assuming the composite as a homogeneous material. Deng et al 26 presented a novel analytical model to predict the cutting forces in micromilling of this material considering particle debonding caused by interface failure.…”
Section: Introductionmentioning
confidence: 99%